The Effectiveness of Monetary Policy Transmission Under Capital Inflows : Evidence from Asia - Jain-Chandra, Sonali; Unsal, Filiz (Washington, D.C. : International Monetary Fund, 2012)
The effectiveness of the monetary policy transmission mechanism in open economies could be impaired if interest rates are driven primarily by global factors, especially during periods of large capital inflows. The main objective of this paper is to assess whether this is true for emerging Asia's economies. Using a dynamic factor model and a structural vector auto-regression model, we show that long-term interest rates in Asia are indeed predominantly driven by global factors. However, monetary policy transmission mechanism remains effective in the region, as it operates predominantly through short-term interest rates. Nevertheless, the monetary transmission mechanism, though effective, is somewhat weaker in Asia during the periods of surges in capital inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet